Protective effect of exercise on animals with sepsis: a systematic review of the existing literature - Na Yang; Nan Jiang; Chunming Shen; Ming Gao; Qian Tong; Jian Sun (BMC Infectious Diseases)
Abstract Background Sepsis often led to multiple organ dysfunction (MODS) and even death. Although a variety of medicine were used to treat sepsis in clinic, there was still no specific and effective clinical medicine treatment. Exercise had been shown to work on MODS. However, in preclinical studies, there was no systematic evidence to summarize the effects of exercise training on sepsis. Objectives To investigate the effects of exercise training on sepsis in preclinical studies and explore possible mechanisms to provide reliable preclinical evidence for the use of exercise training in sepsis. Method Preclinical studies were retrieved from electronic databases (Pubmed, Embase, Cochrane Library, Scopus, Medline, Web of science) as of June 25, 2024. Our review included in vivo English studies evaluating the radioprotective effects of exercise training on sepsis. The quality of each study was assessed using the Center for Systematic Evaluation of Experimental Animal Studies (SYCLE) Animal Research Bias Risk Tool. All results were described comprehensively. Results 17 in vivo studies were included. Our comprehensive descriptive analysis showed that exercise could improve the general condition, lung injury, liver injury, kidney injury, heart and aortic injury, spleen and thymus injury, and other injuries in animals with sepsis. And its possible mechanisms were involved improving the general condition of sepsis animals, pathological and cell number of organs, anti-inflammation, anti-oxidative stress, anti-DNA damage, and so on. Conclusion Exercise training could protect sepsis by anti-inflammatory, anti-oxidative stress, increased antibacterial ability, reduced cell death, improved metabolism, vital signs and MODS.